Sunlight photolysis of benzotriazoles – Identification of transformation products and pathways. (July 2016) - Weidauer, Cindy; Davis, Caroline; Raeke, Julia; Seiwert, Bettina; Reemtsma, Thorsten
Abstract: Benzotriazoles (BTs) are widely used corrosion inhibitors, incompletely removed in municipal wastewater treatment. The photochemical fate of the three BTs 1H-benzotriazole (1H-BT), 4-methyl-1H-benzotriazole (4Me-BT) and 5-methyl-1H-benzotriazole (5Me-BT) and of three microbial metabolites, was studied under simulated sunlight (290–800 nm) at neutral pH in aqueous solution for 24 h. The half-life, the quantum yield and the reaction rate were determined and a total of 36 photolysis products were detected and identified using liquid chromatography-high resolution-mass spectrometry. The half-lives of all six BTs were in the range of 6–24 h under the experimental conditions. Though the quantum yields were comparatively low (0.0007–0.0021), the environmental half-lives ranged from 2.4 to 8 d, suggesting that sunlight photolysis is still a relevant degradation process of BTs in surface waters. The photolysis pathway of 1H-BT under simulated sunlight differed from that suggested for UV-radiation, in that aminophenol is formed directly rather than via aniline. Similar pathways were found for the other BTs, except for 4-hydroxy-1H-benzotriazole (4OH-BT). Most identified transformation products of the BTs showed a high reactivity and appear not to persist in the environment. Upon co-photolysis of BTs with dissolved organic matter (DOM), however, series of reaction products were determined by Fourier transform - ion cyclotron resonance - mass spectrometry (FTICR-MS) which are formed by reaction of photolysis intermediates of the BTs with DOM. Graphical abstract: Highlights: Sunlight photolysis is a relevant degradation process for benzotriazoles in surface water. Photodenitrogenation is the first degradation step (except for 4OH-BT). Most transformation products show a high reactivity or are biodegradable. Some reactive photolysis intermediates react with dissolved organic matter.